ERROR ANALYSIS ON ENGLISH PLURAL NOUNS OF STUDENTS’ SENTENCES - Hansela Nurhani; Ridha Ilma; Renny Kurniasari (PROJECT (Professional Journal of English Education), 2023)
This study was aimed at finding out: the types of error of plural nouns on students’ sentences made by the seventh graders at one of junior high school in Palembang. This study used descriptive quantitative research. The data were collected from four classes of seventh grade students with a total of 129 students by using cluster random sampling. This study focused on analyzing the students’ errors in plural nouns, thus some procedures of error analysis was applied, they were: collection, identification, and classification. The frequencies of errors were calculated in percentage. Based on the result of the analysis, there were 2.057 errors found in students’ answers. Furthermore, it was found that the students made 237 (11.52%) errors in omission, 506 (24.60%) errors in addition, 1314 (63.88%) errors in misformation as the highest one. Keywords:  Error Analysis; Plural Nouns